Native structure of mosquito salivary protein uncovers domains relevant to pathogen transmission - Shiheng Liu; Xian Xia; Eric Calvo; Z. Hong Zhou (Nature Communications, 2023)
Female mosquitoes inject saliva into vertebrate hosts during blood feeding, transmitting mosquito-borne pathogens. Here, cryo-EM of mosquito salivary gland extract uncovers the native SGS1 structure and domains relevant to pathogen transmission.